International Credit Flows and Pecuniary Externalities - Markus Brunnermeier; Yuliy Sannikov (Center for Economic Studies and ifo Institute (CESifo), 2015)
This paper develops a dynamic two-country neoclassical stochastic growth model with incomplete markets. Short-term credit flows can be excessive and reverse suddenly. The equilibrium outcome is constrained inefficient due to pecuniary externalities. First, an undercapitalized country borrows too much since each firm does not internalize that an increase in production capacity undermines their output price, worsening their terms of trade. From an ex-ante perspective each firm undermines the natural terms of trade hedge. Second, sudden stops and fire sales lead to sharp price drops of illiquid capital. Capital controls or domestic macro-prudential measures that limit short-term borrowing can improve welfare.
Keywords: F33; F34; F36; F38; F41; G15; 330; credit flows; capital flows; sudden stops; pecuniary externalities; hot money; Phoenix Miracle; terms of trade hedge